Paranasal Sinus Invasion Should Be Classified as T4 Disease in Advanced Nasopharyngeal Carcinoma Patients Receiving Radiotherapy - Zhao, Yajie; Zhou, Qin; Li, Na; Shen, Liangfang; Li, Zhanzhan (Frontiers in Oncology, 2020)
In this study, we explored the association between paranasal sinus invasion and prognosis in patients with advanced nasopharyngeal carcinoma (NPC, (T3/T4N0–3M0), and assessed the possibility of considering paranasal sinus invasion a T category in the 8th edition of the American Joint Committee on Cancer staging system. We enrolled 352 NPC patients who received intensity-modulated radiotherapy between 2008 and 2012. Clinical characteristics and follow-up data were collected. The incidence of paranasal sinus invasion was 36.4% (128 of 352 patients). Multivariate Cox regression analysis indicated that paranasal sinus invasion and cervical lymphatic metastasis were independent negative prognostic factors for overall survival (OS, P=0.024, P=0.012), progression-free survival (PFS, P=0.007, P=0.007 ), and distant metastasis-free survival (DMFS, P=0.001, P=0.000). The gross tumor volume of the nasopharynx was an independent negative prognostic factor for OS (P=0.013). Cox regression analysis indicated that there were no significant differences in OS, PFS, DMFS, or local relapse-free survival (LRFS) between NPC patients with T4 stage disease and those with T3 and paranasal sinus invasion (P>0.05). The updated T + N staging system slightly improved the prediction of LRFS (0.649, 95% CI: 0.553–0.745) in NPC patients compared to the AJCC system (0.640, 95% CI: 0.545–0.736; P=0.023). Paranasal sinus invasion is independently associated with a poor prognosis in NPC patients. Thus, we recommend that the AJCC staging system upgrade paranasal sinus invasion to the T4 classification.